MicroRNA-378 promotes hepatic inflammation and fibrosis via modulation of the NF-κB-TNFα pathway - Zhang, Tianpeng (J Hepatol, 2018)
BACKGROUND & AIMS: The progression of hepatosteatosis to non-alcoholic steatohepatitis (NASH) is a critical step in the pathogenesis of hepatocellular cancer. However, the underlying mechanism(s) for this progression is essentially unknown. This study was designed to determine the role of miR-378 in regulating NASH progression. METHODS: We used immunohistochemistry, luciferase assays and immunoblotting to study the role of miR-378 in modulating an inflammatory pathway. Wild-type mice kept on a high-fat diet (HFD) were injected with miR-378 inhibitors or a mini-circle expression system containing miR-378, to study loss and gain-of functions of miR-378. RESULTS: MiR-378 expression is increased in livers of dietary obese mice and patients with NASH. Further studies revealed that miR-378 directly targeted Prkag2 that encodes AMP-activated protein kinase γ 2 (AMPKγ2). AMPK signaling negatively regulates the NF-κB-TNFα inflammatory axis by increasing deacetylase activity of sirtuin 1. By targeting Prkag2, miR-378 reduced sirtuin 1 activity and facilitated an inflammatory pathway involving NF-κB-TNFα. In contrast, miR-378 knockdown induced expression of Prkag2, increased sirtuin 1 activity and blocked the NF-κB-TNFα axis. Additionally, knockdown of increased Prkag2 offset the inhibitory effects of miR-378 inhibitor on the NF-κB-TNFα axis, suggesting that AMPK signaling mediates the role of miR-378 in facilitating this inflammatory pathway. Liver- specific expression of miR-378 triggered the development of NASH and fibrosis by activating TNFα signaling. Ablation of TNFα in miR-378-treated mice impaired the ability of miR-378 to facilitate hepatic inflammation and fibrosis, suggesting that TNFα signaling is required for miR-378 to promote NASH. CONCLUSION: MiR-378 plays a key role in the development of hepatic inflammation and fibrosis by positively regulating the NF-κB-TNFα axis. MiR-378 is a potential therapeutic target for the treatment of NASH.